EMPOWERING WOMEN FOR SUSTAINABLE CAREER DEVELOPMENT IN NAGALAND A COMPREHENSIVE REVIEW - Nagi, Pelenino; Kaushal, Rekha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This comprehensive review examines the multifaceted challenges and opportunities surrounding the empowerment of women for sustainable career development in Nagaland, a culturally rich and diverse state in northeastern India. Drawing upon a systematic literature search and analysis, this review synthesizes existing research and identifies key factors influencing women’s access to education, employment, and entrepreneurship in the region. The review highlights the intersectional nature of gender disparities, emphasizing the role of traditional gender norms, socio-economic factors, and cultural practices in shaping women’s career trajectories. By critically analysing the existing literature, this review aims to provide valuable insights into the challenges faced by women in Nagaland and identify opportunities for promoting sustainable career development. Empowering women for sustainable career development in Nagaland requires a thorough understanding of the socio-cultural, economic, and institutional factors that shape women’s access to and advancement in career paths. This comprehensive review aims to explore these factors and shed light on the existing challenges faced by women in Nagaland regarding career development. The findings highlight the importance of addressing socio-cultural norms, economic disparities, and institutional support systems to create an environment conducive to women’s empowerment and sustainable career growth in Nagaland.